Fabrication and properties of plasma-sprayed Al 2O 3/ZrO 2 composite coatings - Dejang N. (2014)
Al 2O 3/xZrO 2 (where x = 0, 3, 13, and 20 wt.%) composite coatings were deposited onto mild steel substrates by atmospheric plasma spraying of mixed α-Al 2O 3 and nano-sized monoclinic-ZrO 2 powders. Microstructural investigation showed that the coatings comprised well-separated Al 2O 3 and ZrO 2 lamellae, pores, and partially molten particles. The coating comprised mainly of metastable γ-Al 2O 3 and tetragonal-ZrO 2 with trace of original α-Al 2O 3 and monoclinic-ZrO 2 phases. The effect of ZrO 2 addition on the properties of coatings were investigated in terms of microhardness, fracture toughness, and wear behavior. It was found that ZrO 2 improved the fracture toughness, reduced friction coefficient, and wear rate of the coatings. © ASM International.